MAS’ industrial policy (2006-2019): an institutional approach to the limits of structural change in Bolivia - De-la-Cruz-Prego, Fernando (Iberoamerican Journal of Development Studies, 2021)
In the paper, it is analysed the industrial policies in Bolivia during the successive governments of the MAS party (2006-2019). Specifically, it is focused on the institutional dimension of industrial policies and on the hypothesis that institutional problems have been a determining factor in the inability of the new model to translate its policies into structural transformations of the productive economy. For this, an analysis is articulated in four levels of industrial policy: normative-strategic, institutional, sectoral policies, and instruments-incentives. In the analysis, it is showed that there are various design and implementation failures at the institutional level (prioritization of primary sectors, absence of public-private partnerships, regulatory overlaps, limited bureaucratic capabilities, or absence of a technological innovation system, among others), that have made it impossible to industrialization and structural change in Bolivia.